How to influence people make a difference in your world - Maxwell, John C. (California Thomas Nelson, 2013)
Believe it or not, the most effective way to make an impact on the world is to make an impact on individual people. How do you do that? Through influence.
Unabridged
Keywords: Influence (Psychology)